An Improved Synthesis of 2-, 3-, and 4-(Trifluoromethyl)cyclohexylamines - Alekseenko, Anatoliy N.; Denis, Klukovsky; Lukin, Oleg; Mykhailiuk, Pavel K.; Shishkin, Oleg V.; Pustovit, Yurii M. (Synthesis, 2012)
An improved synthesis of 2-, 3-, and 4-trifluoromethylcyclohexylamines on a multigram scale via PtO2-mediated hydrogenation of the corresponding trifluoromethylanilines in trifluoroacetic acid at room temperature under atmospheric pressure is reported. The hydrogenation occurred with a remarkable stereoselectivity favoring the formation of cis-isomers.
Keywords: trifluoromethyl group; amines; cyclohexyl group; hydrogenation; trifluoroacetic acid